2021
DOI: 10.21203/rs.3.rs-696660/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commensal Gut Bacterium Akkermansia Muciniphila Secretome Induces Mitochondrial Calcium Overload and α-Synuclein Aggregation in Enteroendocrine Cells

Abstract: Background: The notion that the gut microbiota plays a role in neurodevelopment, behavior and outcome of neurodegenerative disorders is recently taking place. A number of studies have consistently reported a greater abundance of Akkermansia muciniphila in Parkinson’s disease (PD) fecal samples. Nevertheless, a functional link between A. muciniphila and sporadic PD remained unexplored. Here, we investigated whether A.muciniphila conditioned medium could initiate the misfolding process of α-synuclein (αSyn) in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Earlier studies showed that EEC exhibit neuronal features with the presence of axonlike basal processes and the expression of neuronal proteins such as synapsin 1, PGP9.5 and neurofilaments (Bohórquez et al, 2014(Bohórquez et al, , 2015. Our identification of tau in EEC further expands the neuronal repertoire of EEC and echoes recent publications which showed that alphasynuclein is also expressed in EEC (Chandra et al, 2017;Casini et al, 2021;Amorim Neto et al, 2022). The observation that alpha-synuclein EEC lie in close proximity to alpha-synucleinexpressing enteric neurons led Liddle and collaborators to posit that the EEC might be critically involved in the circuit between the gut lumen and the brain for the bottom-up propagation of PD pathology (Chandra et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Earlier studies showed that EEC exhibit neuronal features with the presence of axonlike basal processes and the expression of neuronal proteins such as synapsin 1, PGP9.5 and neurofilaments (Bohórquez et al, 2014(Bohórquez et al, , 2015. Our identification of tau in EEC further expands the neuronal repertoire of EEC and echoes recent publications which showed that alphasynuclein is also expressed in EEC (Chandra et al, 2017;Casini et al, 2021;Amorim Neto et al, 2022). The observation that alpha-synuclein EEC lie in close proximity to alpha-synucleinexpressing enteric neurons led Liddle and collaborators to posit that the EEC might be critically involved in the circuit between the gut lumen and the brain for the bottom-up propagation of PD pathology (Chandra et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…EECs are emerging as a critical mediator of the gut−brain axis 59,60 and have been implicated in PD as a source of intestinal α-syn. 4,52 Since EECs can form synapses with the enteric nervous system, 59 it has been hypothesized that α-syn aggregates may spread from EECs to the brain via the vagus nerve; 4,52 however, the precise molecular stimuli of α-syn aggregation in EECs have remained elusive. Owing to our findings that nitrite induces dopamine-dependent α-syn aggregation in vitro, we suspected that nitrite could induce the same process in EECs.…”
Section: ■ Discussionmentioning
confidence: 99%
“…51 Thus, EECs have been proposed as a potential site where environmental factors, including bacterial metabolites, could initiate α-syn misfolding and the prion-like cascade leading to PD. 4,52 Owing to gut epithelial cells absorbing nitrite through passive diffusion, 53 we hypothesized that this redox-active metabolite that is produced in the gut lumen by nitraterespiring bacteria 18,19 could induce aggregation of α-syn that is present in the cytoplasm of EECs. 4 To test our hypothesis, we used murine STC-1 cells, an accepted model cell line for elucidating properties of native EECs.…”
Section: E Coli Nitrate Respiration Initiates a Cascade Of Oxidation ...mentioning
confidence: 99%
“…The mechanism of formation of pathological α-synuclein in response to the imbalanced gut microbiota remains elusive, albeit we hypothesize here the role of EECs as a possible target given that they are directly exposed and respond to microbes and microbial metabolites 67,68 . Recently it has been demonstrated that Akkermansia muciniphila, a bacterial strain residing in the gastrointestinal tract and associated with PD, led to α-synuclein aggregation in an enteroendocrine cell line 69 . Therefore, although the specific habitat for pathological α-synuclein in the gut is unknown, our identification of α-synuclein in EECs and the location of EECs at the interface between the gut lumen, rich with microbiota and enteric nerve fibers, has raised the possibility that EECs may be a source for the formation and possible spread of pathological αsynuclein 46 .…”
Section: Discussionmentioning
confidence: 99%